DNA Damage Repair and Drug Efflux as Potential Targets for Reversing Low or Intermediate Ciprofloxacin Resistance in E. coli K-12 - Klitgaard, Rasmus N.; Jana, Bimal; Guardabassi, Luca; Nielsen, Karen L.; Løbner-Olesen, Anders (Frontiers in Microbiology, 2018)
Ciprofloxacin is a potent antibacterial drug that is widely used in human clinical applications. As a consequence of its extensive use, resistance has emerged in almost all clinically relevant bacterial species. A mean to combat the observed ciprofloxacin resistance is by reversing it via co-administration of a potentiating compound, also known as a helper drug. Here, we report on the current advances in identifying ciprofloxacin helper drugs, and put them into perspective of our own findings. We searched for potential helper drug targets in Escherichia coli strains with different levels of ciprofloxacin resistance using transcriptomics i.e. RNAseq and by deletion of genes associated with hyper-susceptibility to ciprofloxacin. Differential gene expression analysis of the highly ciprofloxacin resistant uropathogenic E. coli strain, ST131 UR40, treated with a clinically relevant concentration of ciprofloxacin (2 µg/mL), showed that the transcriptome was unaffected. Conversely, genetic screening of 23 single gene deletions in the high-level ciprofloxacin resistant laboratory derived E. coli strain, LM693, led to a significant decrease in the minimal inhibitory concentration for several genes, including genes encoding the AcrAB-TolC efflux pump, SOS-response genes and the global regulator fis. In addition, deletion of acrA, tolC, recA or recC rendered two E. coli strains with intermediate susceptibility to ciprofloxacin fully susceptible according to the CLSI recommended breakpoint. Our results corroborate the AcrAB-TolC efflux pump and the SOS response proteins, RecA and RecC, as potential targets for ciprofloxacin helper drugs in treatment of human bacterial infections caused by E. coli strains with intermediate sensitivity to ciprofloxacin.